2023
DOI: 10.3748/wjg.v29.i14.2114
|View full text |Cite
|
Sign up to set email alerts
|

Challenges in pediatric inherited/metabolic liver disease: Focus on the disease spectrum, diagnosis and management of relatively common disorders

Abstract: The clinical scenario of pediatric liver disease is becoming more intricate due to changes in the disease spectrum, in which an increasing number of inherited/ metabolic liver diseases are reported, while infectious diseases show a decreasing trend. The similar clinical manifestations caused by inherited/metabolic diseases might be under-recognized or misdiagnosed due to nonspecific characteristics. A delayed visit to a doctor due to a lack of symptoms or mild symptoms at an early stage will result in late dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 101 publications
0
4
0
Order By: Relevance
“…About 20% of pediatric liver transplants are performed for single-gene liver diseases, and almost half of chronic liver diseases that manifest in childhood have a genetic basis ( 27 ). Clinical features that are similar and caused by IMLDs may be under-recognized or misdiagnosed due to their non-specific nature ( 4 ). This study observed that IMLD presents a range of clinical manifestations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…About 20% of pediatric liver transplants are performed for single-gene liver diseases, and almost half of chronic liver diseases that manifest in childhood have a genetic basis ( 27 ). Clinical features that are similar and caused by IMLDs may be under-recognized or misdiagnosed due to their non-specific nature ( 4 ). This study observed that IMLD presents a range of clinical manifestations.…”
Section: Discussionmentioning
confidence: 99%
“…In our cohort, out of the 1,111 cases with an unknown diagnosis, only 35.3% underwent genetic testing and only 17.1% underwent liver biopsy, owing to limited resources. Furthermore, as 80.1% of the cases occurred during infancy, the restricted diagnostic options available, combined with vague or non-existent symptoms, make it challenging to determine the cause ( 4 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been recently discovered that vitamin D [10] and melatonin [11] have been shown to improve liver function in children with nonalcoholic fatty liver disease (NAFLD). Vitamin D has garnered specific attention as one of the contributing factors of autoimmunity because it acts as an immunomodulator and inhibits inflammation by reducing T and B cell auto-aggression.…”
Section: Introductionmentioning
confidence: 99%